The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1088/0031-8949/85/05/055702
|View full text |Cite
|
Sign up to set email alerts
|

The nonlinear optical rectification coefficient in a hydrogenic quantum ring

Abstract: The second-order nonlinear optical rectification coefficient (ORC) associated with intersubband transitions in a hydrogenic quantum ring (QR) with a two-dimensional pseudopotential in the presence of an external magnetic field is theoretically investigated. Calculations are performed by using the perturbation method and the compact density-matrix approach within the effective mass approximation. Based on the computed energies and wave functions, we have investigated the effects of the hydrogenic impurity, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To our knowledge, there are only a few research articles related with the effects of impurity and external influences on linear and nonlinear optical properties of QRs [11,19]. The linear and the third-order nonlinear optical absorption spectra of a donor impurity confined within a QR with a parabolic potential have been investigated in [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are only a few research articles related with the effects of impurity and external influences on linear and nonlinear optical properties of QRs [11,19]. The linear and the third-order nonlinear optical absorption spectra of a donor impurity confined within a QR with a parabolic potential have been investigated in [11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have found that the modifications in the confinement strength, the incident optical density, and the ring radius have a great effect on the linear, the third-order nonlinear, and total absorption spectra. Furthermore, the second-order nonlinear optical rectification coefficient associated with intersubband transitions in a hydrogenic QR system with a two-dimensional pseudopotential in the presence of an external magnetic field is theoretically investigated in [19]. In that case, the calculations are performed using the perturbation method and the compact effective mass density matrix approach.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous eect of impurity and external inuences on the linear and nonlinear optical properties of semiconductor nanostructures has also been considered in recent years [2,3]. So far, there are only a few published research articles related with the eects of impurity and external inuences on linear and nonlinear optical properties of semiconductor quantum rings (QRs) [4,5]. On the other hand, the use of delta-doping techniques allows the creation of high-density two-dimensional electron gases [68], providing a suitable environment for the increase in the conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors studied the simultaneous effects of hydrogenic donor impurity and external perturbations, such as electric and magnetic fields and hydrostatic pressure, on the linear and nonlinear optical properties of semiconductor nanostructures, particularly in the case of semiconductor quantum dots [8][9][10][11][12][13][14][15][16][17]. There are also some research papers related with the effects of shallow-impurities and external influences on the linear and nonlinear optical properties in QRs [18][19][20]. Xie has investigated the linear and the third-order nonlinear optical absorption spectra of a donor impurity confined within a QR with a parabolic potential [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the second-order nonlinear optical rectification coefficient associated with intersubband transitions in a hydrogenic QR system with a two-dimensional pseudopotential in the presence of an external magnetic field is theoretically studied in Ref. [19]. In that case, the calculation exploits the perturbation method.…”
Section: Introductionmentioning
confidence: 99%